Health care users’ acceptance of broad consent for storage of biological materials and associated data for research purposes in Uganda [version 2; peer review: 1 approved, 3 approved with reservations] - Semanda Patrick; Mugalula Flaviano; Ssewanyana Isaac; Hellen Nansumba; Douglas Wassenaar (Wellcome Open Research, 2022)
Background: Implementation of appropriate informed consent has become a cornerstone for the use of biological materials and data from clinical care to use in research. During 2017-2018, the Ugandan National Biorepository has since sought prior informed consent for long-term storage and use of remnant clinical human biological materials, where a shortened informed consent form (ICF) was incorporated on the laboratory investigation form. This project aimed at determining the acceptability rate of broad consent from health care users (HCUs) for storage of biological materials and data for research purposes in Uganda. Methods: A cross-sectional study was conducted at three Primary Health Care Facilities. 500 HCUs above 18 years of age seeking health care at outpatient departments between March to December 2020 were invited to enrol. A shortened experimental ICF for this study was developed and attached to the Laboratory investigation form. Results: Overall the acceptability of broad consent for storage of biological materials and data was 86.2% [95% CI: 82.9%-88.9%]. Compared to participants who perceived that the informed consent information is understandable (OR=0.10, CI [0.03-0.32], participants who either partly or totally disagreed were significantly less likely to perceive information as understandable (OR=0.27, CI [0.15-0.46]. 226 out of 431 respondents that accepted storage of biological materials and data, majority (61.7%) preferred to receive feedback on results of relevance to their health. Conclusion: Acceptance of broad consent for storage of biological materials and data for future research purposes was high among HCUs. A shortened and simplified ICF may trigger discussions between participants and health care workers hence increase research participant understanding of study related materials in biobanking. This in turn could enrich ethically collected biobank resources for future research of public health relevance.